Taste perception and coding in Drosophila. - Thorne, N.; Chromey, C.; Bray, S.; Amrein, H. (Current Biology, 2004)
Discrimination between edible and contaminated foods is crucial for the survival of animals. In Drosophila, a family of gustatory receptors (GRs) expressed in taste neurons is thought to mediate the recognition of sugars and bitter compounds, thereby controlling feeding behavior.We have characterized in detail the expression of eight Gr genes in the labial palps, the fly's main taste organ. These genes fall into two distinct groups: seven of them, including Gr66a, are expressed in 22 or fewer taste neurons in each labial palp. Additional experiments show that many of these genes are coexpressed in partially overlapping sets of neurons. In contrast, Gr5a, which encodes a receptor for trehalose, is expressed in a distinct and larger set of taste neurons associated with most chemosensory sensilla, including taste pegs. Mapping the axonal targets of cells expressing Gr66a and Gr5a reveals distinct projection patterns for these two groups of neurons in the brain. Moreover, tetanus toxin-mediated inactivation of Gr66a- or Gr5a-expressing cells shows that these two sets of neurons mediate distinct taste modalities-the perception of bitter (caffeine) and sweet (trehalose) taste, respectively.Discrimination between two taste modalities-sweet and bitter-requires specific sets of gustatory receptor neurons that express different Gr genes. Unlike the Drosophila olfactory system, where each neuron expresses a single olfactory receptor gene, taste neurons can express multiple receptors and do so in a complex Gr gene code that is unique for small sets of neurons.